DESAIN RUANG BERMAIN ANAK USIA DINI SEBAGAI STRATEGI PENGEMBANGAN KARAKTER ANAK - Siti Zulfa Yuzni (JURNAL TEMATIK, 2020)
Playing is an activity carried out from the children in an early age and by playing activity children gain an experience and learning. In playing activity children would feel joy, pleasure, and heerfulness, so that it could develop cognitive abilities, social cultural abilities, physical abilities, motor skills, emotional abilities and abilities intellectual. Every child has the right to space for play activities that can support development and growth before adulthood. Based on this it is necessary early childhood playroom design that can accommodate play and learning activities. The design of the formed space consists of inner and outer spaces. Spatial design is reviewed based on consideration of the shape of the room, color and texture, and movement of children. With the existence of a child's playroom, a child can develop creativity, skills and knowledge through movement, imagination and expressions based on children's behavior, so that the child's growth and development can take place well. This is done as strategy in the development of children's character.